Field Evaluation of BAU-Biofungicide and Plant Extracts in Controlling Leaf Blight of Wheat Caused by Bipolaris sorokiniana - Khan, Md. Aminul Islam; Hossain, Ismail; Ahmad, M. U.; Monjil, Mohammad Shahjahan (Journal of the Bangladesh Agricultural University, 2024)
Field evaluation of BAU-Biofungicide and plant extracts was performed to manage leaf blight of wheat caused by Biopolaris sorokiniana from November, 2015 to April, 2018. Two susceptible varieties of wheat viz.,Kanchan and Prodip were used in the experiment. Aqueous extracts of Neem leaf and garlic clove, Trichoderma based preparation BAU-Biofungicide, an inducer Bion were evaluated in the field as seed-treatment or seed-treatment along with foliar application. In addition, a chemical fungicide (Tilt) was used as positive control and an untreated negative control were included in the experiment. Based on the three years of experiment in three cropping seasons during 2015-16, 2016-17 and 2017-18; seed treatment with BAU-Biofungicide reduced leaf blight severity in both cultivars. The lowest disease severity was observed in plots where Tilt was used as spray followed by seed treatment with BAU-Biofungicide plus BAU-Biofungicide spray. BAU-Biofungicide showed better performance in controlling leaf blight of wheat. Based on the findings of the present study, BAU-Biofungicide potentially reduce the severity of Bipolaris leaf blight of wheat therefore, it could be an effective option for the growers for eco-friendly management of leaf blight disease of wheat and obtaining higher yield. J Bangladesh Agril Univ 18(4): 916–922, 2020 https://doi.org/10.5455/JBAU.110205